KAJIAN PENAMBAHAN TEPUNG TAPIOKA DAN KUNING TELUR PADA PEMBUATAN BAKSO DAGING SAPI - Basuki, Enny Karti; Latifah, Ir.; Wulandari, Ika Emi (UPN VETERAN JAWA TIMUR, 2012)
ABSTRACT Meat ball is one of the emulsion food. Meat ball dough is oil in water emulsion made from fat and water mixed in colloid phase, with protein as emulsifier. Research aim on the effect of cassava flour (binder) and yolk addition on the quality of meat ball has been conducted. This research used Factorial Randomized Design consisting of two factors and two replications. The first factor is yolk addition (20, 35, 50 and 65 grams) and the second factor is cassava flour addition (10, 12, 5, 15 and 17,5 gram). The best treatment is combination of yolk 35 grams and cassava flour 12,5 gram. This meat ball product has emulsion stability (oil separated) : 1,24% water content : 65,60%, protein : 10,29%, fat : 4,57%, texture value : 0,4465 mm/gr.dt. WHC value : 86,80%, taste score : 4,20, flavour score : 2,65 and texture score : 3,65, colour score : 2,68.Key words : meat ball, cassava flour, emulsion, yolk.